Dioxygen-induced oxidative activation of a P–H bond: radical oxyphosphorylation of alkenes and alkynes toward β-oxy phosphonates. Issue 83 (29th September 2016) - Peng, Pan; Lu, Qingquan; Peng, Long; Liu, Chao; Wang, Guangyu; Lei, Aiwen
Abstract : The dioxygen-induced radical oxyphosphorylation of alkenes and alkynes is presented, wherein a P–H bond was activated by molecular oxygen. Abstract : The dioxygen-induced radical oxyphosphorylation of alkenes and alkynes is presented, wherein a P–H bond was activated by molecular oxygen. Various β-oxy phosphonates could be facilely synthesized without the assistance of any transition metals or extra organic initiators. Mechanistic studies showed that HP(O)Ph2 acts as a reductant to accelerate oxyphosphorylation.